Conceptual principles of formation marketing strategy of agricultural enterprises in the conditions of wartime - Полозова, Т. В.; Мурзабулатова, О. В.; Красноруцький, О. О.; Маренич, Т. Г.; Марченко, В. А. (My University, 2023)
The article is devoted to the characteristics and justification of improving the mechanism of formation of the marketing strategy of agrarian enterprises in wartime conditions. It was determined that the marketing strategy acquires the status of a priority in the system of enterprise strategies and should be organically combined with the overall corporate strategy. It was found that there are different approaches to revealing the essence of the terms "marketing", "marketing management", and "marketing strategy", which require their author's definition. In the article, marketing is understood as a complex of the enterprise's current organizational and management actions, aimed at using the exchange to meet the real needs, requirements, and wishes of consumers and achieve the goals of the manufacturer (seller) with an orientation to social ethics. It has been proven that marketing strategy is a separate concept with its own goals and tools for achievement, which is focused on creating an appropriate system of relationships with consumers. At the same time, the marketing strategy of an enterprise is defined in a broad sense as a set of ideas regarding general, non-detailed ways of creating or changing consumer perceptions of a product over a specified period using available marketing tools and available resources in certain competitive conditions, which allows the enterprise to achieve commercial success and general goals. It is advisable to form the marketing strategy of an agricultural enterprise based on the basic concept of its development and consider resources and opportunities, the state and features of competition, demand trends, external environmental conditions, and internal factors in the relationship. It was concluded that when developing a clear and understandable marketing strategy, it is crucial to set achievable and measurable development goals, use only verified data when analyzing the current state of the market and one's own capabilities, find alternatives, and approach solving problems creatively and creatively. Each aspect of the agribusiness marketing strategy is suggested to be viewed digitally. It was determined that the primary goal of the marketing strategy in a "peaceful" time is to obtain the maximum profit to achieve a sustainable competitive advantage due to the understanding of consumer needs and market realities. In wartime - continuity, and profitability of production, preservation of jobs, payment of wages, provision of logistics, and building relationships of trust, support, and care with buyers and customers. It is well-founded that marketing underwent significant transformations during the war, and accordingly, the principles of developing its strategy also changed. The principles of marketing strategy formation in agricultural enterprises in wartime conditions include the following: social orientation; justified riskiness; flexibility and maneuverability (adaptability); concentration of efforts on current areas of marketing activity; focus on obtaining results in the short term; relationship and interdependence of strategy and tactics. Стаття присвячена характеристиці та обґрунтуванню вдосконалення механізму формування маркетингової стратегії аграрних підприємств в умовах воєнного часу. Визначено, що маркетингова стратегія набуває статусу пріоритетної в системі стратегій підприємства та має органічно поєднуватися із загально корпоративною стратегією. З’ясовано, що існують різні підходи до розкриття сутності термінів «маркетинг», «маркетинговий менеджмент», «маркетингова стратегія», що вимагало авторського їх визначення. Під маркетингом в статті розуміється комплекс актуальних організаційно-управлінських дій підприємства, спрямованих на використання обміну для задоволення реальних потреб, вимог, побажань споживачів і досягнення цілей виробника (продавця) з орієнтацією на соціальну етичність. Доведено, що маркетингова стратегія є окремим поняттям із власними цілями та інструментами їх досягнення, що сфокусоване на створенні відповідної системи взаємовідносин із споживачами. При цьому маркетингову стратегію підприємства у широкому сенсі визначено як сукупність ідей щодо загальних недеталізованих способів створення чи зміни уявлень споживачів про продукт за визначений проміжок часу за допомогою доступних маркетингових інструментів та наявних ресурсів у певних конкурентних умовах, що дозволяє підприємству досягнути комерційного успіху та загальних цілей. Маркетингову стратегію аграрного підприємства доцільно формувати на основі базової концепції його розвитку та враховувати при цьому ресурси та можливості, стан і особливості конкуренції, тенденції попиту, умови зовнішнього середовища та внутрішні фактори у взаємозв’язку. Зроблено висновок, що розробляючи чітку та зрозумілу маркетингову стратегію, важливо ставити досяжні та вимірні цілі розвитку, при аналізі поточного стану ринку та власних можливостей використовувати тільки перевірені дані, знаходити альтернативи, підходити до розв’язання проблем творчо та креативно. Кожен аспект маркетингової стратегії агробізнесу пропонується розглядати через цифрову призму. Визначено, що головна мета маркетингової стратегії в «мирний» час – отримання максимального прибутку, досягнення стійкої конкурентної переваги за рахунок розуміння потреб споживачів і реалій ринку; у воєнний час – безперервність і беззбитковість виробництва, збереженість робочих місць, виплата заробітної плати, забезпечення логістики, вибудовування з покупцями і замовниками відносин довіри, підтримки та турботи. Обґрунтовано, що маркетинг у період воєнних дій зазнав суттєвих трансформацій, відповідно і принципи розробки його стратегії теж змінилися. До принципів формування маркетингової стратегії в аграрних підприємствах в умовах воєнного часу віднесено такі: соціальна спрямованість; виправдана ризикованість; гнучкість та маневреність (адаптивність); концентрація зусиль на поточних напрямах маркетингової діяльності; спрямованість на отримання результату в короткостроковій перспективі; взаємозв’язок та взаємообумовленість стратегії та тактики.
Концептуальні принципи формування маркетингової стратегії сільськогосподарських підприємств в умовах воєнного часу
Keywords: marketing; marketing strategy; marketing management; marketing tools; principles of marketing strategy formation; marketing plan; agricultural enterprises; маркетинг; маркетингова стратегія; маркетинговий менеджмент; маркетингові інструменти; принципи формування маркетингової стратегії; маркетинговий план; аграрні підприємства